Pengaruh Fasilitas Ruang Tunggu Keberangkatan Terhadap Kepuasan Pengguna di Bandar Udara Rahadi Oesman Ketapang Provinsi Kalimantan Barat - Dona Adelia; Eka Prayudhista (Program Studi Magister Ilmu Manajemen Sekolah Tinggi Ilmu Ekonomi Sultan Agung, 2023)
Rahadi Oesman Airport is located in Ketapang City, West Kalimantan. It is a small airport with limited flight routes. The airport is equipped with waiting room facilities for customer needs. The completeness of these facilities can influence user satisfaction. The objective of this study is to determine the impact of the waiting room facility on user satisfaction. The research method employed is quantitative, and the study utilizes a sample size of 100 respondents, which represents the existing population. The validity test involves the use of the product-moment correlation technique at a significance level of 5% (0.05), with a critical value of r = 0.196. The reliability test is conducted using Cronbach's Alpha. The analysis technique utilized in this study is simple linear regression. The findings indicate a significant effect of the waiting room facilities on user satisfaction, with a coefficient of determination of 67.3%.